CONTINUOUS FOUNTAIN CS STANDARD: STABILITY AND ACCURACY ISSUES - Joyet, Alain; Mileti, Gaetano; Thomann, Pierre; Dudle, G. (Middlesex UK: Patrick Gill, 2002)
We describe a primary fountain frequency standard operating with a continuous beam of laser-cooled Cs atoms. In such a device, aliasing effects, which may degrade the short-term stability in pulsed fountains, are removed and atomic-noise limited stability can be achieved with a state-of-the art, but commercially available, local oscillator. The present experimental short-term stability is measured to be 2.5 · 10-13τ-1/2. Another feature of the continuous fountain is the reduced atomic density and higher beam temperature which reduces the collisional shift of the atomic frequency below the 10-15 level. The light-shift is an undesirable characteristic of the continuous operation. Without a light-trap, a light-shift of the order of 10-12 has been measured. The shift is stable enough not to affect the frequency stability to 104 seconds (2.5 · 10-15). A rotating light-trap has been constructed and tested to bring the light-shift and the corresponding uncertainty to a negligible level. Various contributions to the accuracy are studied.